Creativity and history in the life of Saint Maurus - Wickstrom, John B. 1941- (Revue bénédictine, 2016)
The Life of St. Maurus, the first disciple of St. Benedict, tells the story of how the young oblate was raised up in the monastic life at Montecassino, and then sent to France where he established the first Benedictine monastery outside Italy, at Glanfeuil on the Loire. It was purportedly written by a certain Faustus, a companion of St. Maurus on the journey. However, modern scholarship has judged the work to be a forgery by Odo, abbot of Glanfeuil in the mid-9th century. This article, attentive to recent studies of monastic memory, argues that significant elements of this vita were not fictional but constituted reconstructions of communal memories and traditions from the monastery’s early history. The article’s conclusions flow from a close reading of Odo’s Life of Maurus and other Carolingian sources.